Penyelesaian Kasus Pertanahan PT. Pertiwi Lestari dengan Masyarakat Margakaya, Telukjambe Barat, Karawang melalui Resettlement - Ismail Hasan; Tjahjo Arianto; Aristiono Nugroho (Tunas Agraria, 2019)
Abstract: Overlapping case of land tenure and land ownership between the farming community on the Veterans Legion of the Republic of Indonesia (LVRI) and PT. Pertiwi Lestari located in Margakaya Village, Telukjambe Barat Sub-District, Karawang District. PT. Pertiwi Lestari has Hak Guna Bangunan No. 5/ Margamulya with area 328.2 ha located on the settlement land of Cijambe, Margakaya village. LVRI community takes legal action by submitting a lawsuit to the PTUN. The lawsuit at the stage of the Judicial Review in the Supreme Court could not accept the lawsuit of the LVRI community. Conflict resolution through the judiciary is not fully acceptable to the parties to the conflict, so the parties conduct peace deliberations with one solution to the conflict, namely resettlement of 50 LVRI community families who do not have a place to live due to the land case that occurred. This research was conducted with a qualitative method with a descriptive approach. The results of this study indicate that with this resettlement, as many as 50 LVRI community families obtain certainty of tenure, ownership, use and utilization of land in a new place. the compatibility of characteristics between the residents of Margakaya Village, the majority of which are farmers and farm laborers with resettled communities, making the resettlement community not having difficulty in adapting. A positive response from the community to settlements through resettlement makes the legal certainty of ownership of the land which the resettlement participant feels directly.Keywords: Land Case, Conflict Solution, ResettlementIntisari: Kasus tumpang tindih penguasaan dan pemilikan tanah antara masyarakat penggarap Legiun Veteran Republik Indonesia (LVRI) dengan PT. Pertiwi Lestari yang terletak di Desa Margakaya Kecamatan Telukjambe Barat Kabupaten Karawang seluas 328,2 Ha ternyata di lapangan berada di tanah permukiman Kampung Cijambe Desa Margakaya. Masyarakat LVRI kemudian menempuh jalur hukum dengan mengajukan gugatan ke PTUN. Gugatan tersebut pada tahap Peninjauan Kembali ditolak oleh Mahkamah Agung. Para pihak melakukan musyawarah perdamaian dengan salah satu solusi konflik yaitu me-resettlement 50 KK masyarakat LVRI yang tidak memiliki tempat tinggal akibat kasus pertanahan yang terjadi. Penelitian ini dilakukan dengan metode kualitatif dengan pendekatan deskriptif. Hasil penelitian menunjukan bahwa dengan resettlement ini, sebanyak 50 KK masyarakat LVRI mendapatkan kepastian penguasaan, pemilikan, penggunaan, serta pemanfaatan tanah di tempat yang baru. Kesesuaian karakteristik antara penduduk Desa Margakaya yang mayoritas petani dan buruh tani dengan masyarakat yang di-resettlement, menjadikan masyarakat yang di-resettlement tidak kesulitan untuk beradaptasi. Respons positif masyarakat terhadap penyelesaian melalui resettlement membuat kepastian hukum kepemilikan atas tanah dengan yang dirasakan langsung oleh peserta resettlement.Kata Kunci: Kasus Pertanahan, Solusi Konflik, Resettlement